To get the answer you have to add 29.4 and 13.9 and you get 43.3
It is A
Answer:
<h2>C) the length of each shape will alternate between even and odd numbers</h2>
Step-by-step explanation:
the rest are incorrect
Question 7: Choose the correct simplification of the expression (3x − 6)(2x2 − 4x − 5)
Answer:
7. 6x³ - 12x² + 12x + 15
Step-by-step explanation:
(3x-6)(2x² - 4x - 5)
3x • 2x² = 6x³
3x • -4x = -12x²
3x • -5 = -15
-6 • 2x² = -12x²
-6 • -4x = 24x
-6 • -5 = 30
combine terms
6x³ - 12x² - 15 - 12x² + 24x + 30
combine like terms
6x³ - 24x² + 24x + 15
hope this helps :)
in the future, only ask one question per brainly submission. thanks!
The answer is 9 because its an odd number, not the sides of a triangle, can be divided be 3, and is a single digit number.